Evaluation of health surveillance system attributes: the case of neglected tropical diseases in Kenya - Arthur K. S. Ng’etich (BMC Public Health, 2021)
Abstract Background Control of preventive chemotherapy-targeted neglected tropical diseases (PC-NTDs) relies on strengthened health systems. Efficient health information systems provide an impetus to achieving the sustainable development goal aimed at ending PC-NTD epidemics. However, there is limited assessment of surveillance system functions linked to PC-NTDs and hinged on optimum performance of surveillance system attributes. The study aimed to evaluate surveillance system attributes based on healthcare workers’ perceptions in relation to PC-NTDs endemic in Kenya. Methods A cross-sectional health facility survey was used to purposively sample respondents involved in disease surveillance activities. Consenting respondents completed a self-administered questionnaire that assessed their perceptions on surveillance system attributes on a five-point likert scale. Frequency distributions for each point in the likert scale were analysed to determine health workers’ overall perceptions. Data was analysed using descriptive statistics and estimated median values with corresponding interquartile ranges used to summarise reporting rates. Factor analysis identified variables measuring specific latent attributes. Pearson’s chi-square and Fisher’s exact tests examined associations between categorical variables. Thematic analysis was performed for questionnaire open-ended responses. Results Most (88%) respondents worked in public health facilities with 71% stationed in second-tier facilities. Regarding PC-NTDs, respondents perceived the surveillance system to be simple (55%), acceptable (50%), stable (41%), flexible (41%), useful (51%) and to provide quality data (25%). Facility locality, facility type, respondents’ education level and years of work experience were associated with perceived opinion on acceptability (p = 0.046; p = 0.049; p = 0.032 and p = 0.032) and stability (p = 0.030; p = 0.022; p = 0.015 and p = 0.024) respectively. Median monthly reporting timeliness and completeness rates for facilities were 75 (58.3, 83.3) and 83.3 (58.3, 100) respectively. Higher-level facilities met reporting timeliness (p < 0.001) and completeness (p < 0.001) thresholds compared to lower-level facilities. Conclusion Health personnel had lower perceptions on the stability, flexibility and data quality of the surveillance system considering PC-NTDs. Reporting timeliness and completeness rates decreased in 2017 compared to previous surveillance periods. Strengthening all surveillance functions would influence health workers’ perceptions and improve surveillance system overall performance with regard to PC-NTDs.